Pressure‐Induced Photoluminescence Adjustment and Lattice Disorder in Monolayer WSe2. Issue 4 (22nd February 2017) - Gong, Yuanbo; Zhou, Qiang; Huang, Xiaoli; Han, Bo; Fu, Xinpeng; Gao, Hanxue; Li, Fangfei; Cui, Tian
Abstract: Pressure engineering is considered as a novel strategy to modulate the properties of transition metal dichalcogenide materials. Here, through photoluminescence (PL) and Raman measurements, we investigate the electronic band structure variation and lattice vibrational dynamics of monolayer tungsten diselenide (WSe2 ) under pressure. As the pressure increases, the energy of the direct Κ→Κ interband transition increases, whereas that of the indirect Λ→Κ interband transition decreases, leading to a significant transition from direct to indirect band gap at 3.8 GPa. With the increase of pressure, the intensity of the direct Κ→Κ interband transition constantly decreases and finally vanishes around 12.2 GPa. Moreover, a remarkable transition between A′ and LA(M) modes under pressure has been determined by virtue of Raman spectra variations, which indicate a pressure‐induced lattice disorder. This work provides a deep understanding of the intrinsic variation of WSe2 under pressure, which effectively facilitates the development of device applications. Abstract : Exfoliated monolayer WSe2 on a silicon wafer was transferred into a diamond anvil cell chamber for compression. Liquid argon was used as the pressure‐transmitting medium, providing hydrostatic conditions. From the evolution of the Raman spectra, a remarkable transition between A′ and LA(M) modes under pressure was observed, indicating a pressure‐induced lattice disorder.